2022
DOI: 10.1186/s12902-022-00943-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin resistance and thyroid cancer in Chinese euthyroid subjects without conditions affecting insulin resistance

Abstract: Backgrounds In recent years, many studies have shown that insulin resistance is related to the occurrence of thyroid cancer, but there are few reports on whether the two are related under the premise that thyroid function is normal and the metabolic components related to insulin resistance are excluded. This study aims to analyze the insulin resistance of patients with differentiated thyroid cancer after excluding the population with abnormal metabolic components, and to study the risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This may be explained by the influence of Dio2, the enzyme responsible for the conversion of T4 to T3 [ 40 ], which is associated with an increased risk of increased insulin resistance and T2DM [ 39 ]. The results of the present study are in accordance with the outcomes of many studies that have shown no significant associations between DM and other associated predictors (gender, FT4, TSH, thyroid status, hematological indices, vitamin D levels and the ACR TI-RADS scoring system) [ 38 , 58 - 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, some clinical studies reported no significant influence of insulin resistance on the pathogenesis of TNs; hence, some other pathological mechanisms may be more prominent during TN formation and carcinogenesis [ 17 , 44 ]. Our study and many current clinical studies revealed that advanced age is a significant predictor for DM in patients with TNs conducted in China [ 8 - 10 , 38 ], Turkey [ 31 ] and Korea [ 32 ]. This may be explained by the fact that thyroid dysfunction is common in the elderly, which may take on different clinical conditions: clinical and subclinical hypo- and hyperthyroidism, thyroid nodular diseases and thyroid cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations